2020
DOI: 10.1111/rda.13696
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in testicular blood flow dynamics and their relation to systemic and testicular oxidant/antioxidant biomarkers and androgens in rams

Abstract: The environmental temperature increased during summer and decreased during winter to the limits that might negatively affect animal and human reproduction. The responses of Egyptian rams to either hot or cold climatic conditions were studied in six mature rams subjected to weekly testicular Doppler ultrasonographic examination, blood sampling, seminal plasma collection and semen evaluation. The maximum environmental temperature and the relative humidity were used to classify the climatic condition according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 47 publications
1
21
0
Order By: Relevance
“…In the last few years, several studies demonstrated the application of testicular pulsed wave Doppler Ultrasonography as a noninvasive and rapid valuable technique to evaluate the reproductive performance in farm animals (Fávaro et al, 2020;Hedia et al, 2019Hedia et al, , 2020b.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the last few years, several studies demonstrated the application of testicular pulsed wave Doppler Ultrasonography as a noninvasive and rapid valuable technique to evaluate the reproductive performance in farm animals (Fávaro et al, 2020;Hedia et al, 2019Hedia et al, , 2020b.…”
Section: Discussionmentioning
confidence: 99%
“…In the last few years, several studies demonstrated the application of testicular pulsed wave Doppler Ultrasonography as a noninvasive and rapid valuable technique to evaluate the reproductive performance in farm animals (Fávaro et al., 2020; Hedia et al., 2019, 2020b). Testis as a highly compact organ requires a continuous and constant blood flow through the corresponding testicular artery to precisely perform its endocrine (steroidogenesis) and exocrine (sperm production) functions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This experiment was conducted in the Department of Theriogenology, Faculty of Veterinary Medicine, Cairo University, Giza, Egypt, from December 2020 to February 2021 (physiological breeding season in Egypt; Hedia et al., 2020). The Animal Care and Ethical Use Committee of the Faculty of Veterinary Medicine at the Cairo University reviewed and approved the experimental protocol (VetCU28042021264).…”
Section: Methodsmentioning
confidence: 99%